Ethical Development of Artificial Amniotic Sac and Placenta Technology: A Roadmap - Verweij, E. J.; De Proost, Lien; van Laar, Judith O. E. H.; Frank, Lily; Obermann-Borstn, Sylvia A.; Vermeulen, Marijn J.; van Baalen, Sophie; van der Hout-van der Jagt, M. Beatrijs; Kingma, Elselijn (Frontiers in Pediatrics, 2021)
In this paper we present an initial roadmap for the ethical development and eventual implementation of artificial amniotic sac and placenta technology in clinical practice. We consider four elements of attention: (1) framing & societal dialogue; (2) value sensitive design, (3) research ethics and (4) ethical and legal research resulting in the development of an adequate moral and legal framework. Attention to all elements is a necessary requirement for ethically responsible development of this technology. The first element concerns the importance of framing & societal dialogue. This should involve all relevant stakeholders as well as the general public. We also identify the need to consider carefully the use of terminology and how this influences the understanding of the technology. Second, we elaborate on value sensitive design: the technology should be designed based upon the principles and values that emerge in the first step: societal dialogue. Third, research ethics deserves attention: for proceeding with first-in-human research with the technology, the process of recruiting and counseling eventual study participants and assuring their informed consent deserves careful attention. Fourth, ethical and legal research should concern the status of the subject in the AAPT. An eventual robust moral and legal framework for developing and implementing the technology in a research setting should combine all previous elements. With this roadmap, we emphasize the importance of stakeholder engagement throughout the process of developing and implementing the technology; this will contribute to ethically and responsibly innovating health care.